NIR-Absorbing Mesoporous Silica-Coated Copper Sulphide Nanostructures for Light-to-Thermal Energy Conversion - Elisabetta Fanizza; Rita Mastrogiacomo; Orietta Pugliese; Alexa Guglielmelli; Luciano De Sio; Rachele Castaldo; Maria Principia Scavo; Mariangela Giancaspro; Federica Rizzi; Gennaro Gentile; Fabio Vischio; Livianna Carrieri; et al. (Nanomaterials, 2022)
Plasmonic nanostructures, featuring near infrared (NIR)-absorption, are rising as efficient nanosystems for in vitro photothermal (PT) studies and in vivo PT treatment of cancer diseases. Among the different materials, new plasmonic nanostructures based on Cu2−xS nanocrystals (NCs) are emerging as valuable alternatives to Au nanorods, nanostars and nanoshells, largely exploited as NIR absorbing nanoheaters. Even though Cu2−xS plasmonic properties are not linked to geometry, the role played by their size, shape and surface chemistry is expected to be fundamental for an efficient PT process. Here, Cu2−xS NCs coated with a hydrophilic mesoporous silica shell (MSS) are synthesized by solution-phase strategies, tuning the core geometry, MSS thickness and texture. Besides their loading capability, the silica shell has been widely reported to provide a more robust plasmonic core protection than organic molecular/polymeric coatings, and improved heat flow from the NC to the environment due to a reduced interfacial thermal resistance and direct electron–phonon coupling through the interface. Systematic structural and morphological analysis of the core-shell nanoparticles and an in-depth thermoplasmonic characterization by using a pump beam 808 nm laser, are carried out. The results suggest that large triangular nanoplates (NPLs) coated by a few tens of nanometers thick MSS, show good photostability under laser light irradiation and provide a temperature increase above 38 °C and a 20% PT efficiency upon short irradiation time (60 s) at 6 W/cm2 power density.